1993
DOI: 10.1007/bf00159503
|View full text |Cite
|
Sign up to set email alerts
|

Ultracytochemical localization of particulate guanylate cyclase in rat adrenal gland exposed to stimulation by porcine brain natriuretic peptide

Abstract: We studied the cytochemical localization of particulate guanylate cyclase (GC) in rat adrenal gland after stimulation with porcine brain natriuretic peptide (pBNP) by electron microscopy. In the adrenal cortex, GC activity, as demonstrated by the presence of reaction product, was prevalently localized to the zona glomerulosa and zona fasciculata, while the zona reticularis showed little GC reaction product. In the adrenal medulla, GC reaction product was present only in adrenalin-containing cells. All GC posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Recently we detected the presence of rANF and pBNP GC capable of stimulating on intracellular membranes in rat adrenal gland (Rambotti et aL, 1993) and in rat neurohypophysis (Rambotti et al, 1994). A fraction of particulate GC was previously seen on various subcellular membranes (for a review see Tremblay et al, 1988), and intracellular ANF binding sites were detected in some subcellular structures (e.g.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recently we detected the presence of rANF and pBNP GC capable of stimulating on intracellular membranes in rat adrenal gland (Rambotti et aL, 1993) and in rat neurohypophysis (Rambotti et al, 1994). A fraction of particulate GC was previously seen on various subcellular membranes (for a review see Tremblay et al, 1988), and intracellular ANF binding sites were detected in some subcellular structures (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, we have carried out analogous studies on membrane-bound GC activity stimulated by ANF and BNP in several rat organs such as kidney, lung and adrenal gland (Rambotti et al, 1990;Rambotti et al, 1993), in rabbit platelets (Spreca et aI., 1991) and in neurohypophysis (Rambotti et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that acetylcholine (Rodriguez-Pascual et al 1994 and the preganglionic transmitter NPY, present in some ganglion neurons (Schalling et al 1988) as well as in chromaffin cells (Allen et al 1983;Lundberg et al 1983), cause a rapid, transient increase in medullary cGMP levels (Soares-Lemos et al 1997). It may be mentioned that Rambotti et al (1993) have shown that brain natriuretic peptide activates particulate GC, but not the sGC in the adrenal gland, mainly in zona glomerulosa and fasciculata in cortex and in the adrenaline cells of the medulla.…”
Section: Discussionmentioning
confidence: 98%